Glass foam of macroporosity using glass waste and sodium hydroxide as the foaming agent - Bento, André C.; Kubaski, Evaldo T.; Sequinel, Thiago [UNESP]; Pianaro, Sidnei A.; Varela, José Arana [UNESP]; Tebcherani, Sergio M. (Elsevier, 2013)
Glass foams using float glass waste and sodium hydroxide were produced. The influence of the sodium hydroxide amount in the foam formulation was studied. Titanium dioxide was used as a strengthening agent. The variations of temperature, heating rate and sintering time were investigated during the synthesis process. Open porosity was estimated using mercury porosimetry. The morphology of the glass foams was evaluated using scanning electron microscopy, phase formation was studied using X-ray diffraction, and chemical composition was estimated using X-ray fluorescence. As a result, glass foams with macroporosity were obtained. Since the glass foams used glass waste as reactant, the results suggest the development of an alternative route for glass recycling. © 2012 Elsevier Ltd and Techna Group S.r.l.
Keywords: B. Porosity; D. Glass; Sodium hydroxide; Waste treatment; Alternative routes; Chemical compositions; Float glass; Foam formulation; Glass foams; Glass recycling; Glass wastes; Macro-porosity; Mercury porosimetry; Open porosity; Phase formations; Sintering time; Sodium hydroxides; Strengthening agents; Synthesis process; X ray fluorescence; Mercury (metal); Scanning electron microscopy; Sintering; Sodium; Titanium dioxide; X ray diffraction; Glass